A Short Note on a Nonlinear System vibrations under Two Non-Ideal Excitations - Palacios, J. L.; Balthazar, José Manoel [UNESP]; Brasil, R. M L R F (Springer Nature, 2003)
This paper describes a nonlinear phenomenon in the dynamical behavior of a nonlinear system under two non-ideal excitations: the self-synchronization of unbalanced direct current motors. The considered model is taken as a Duffing system that is excited by two unbalanced direct current motors with limited power supplies. The results obtained by using numerical simulations are discussed in details.
Keywords: Non-ideal system; Nonlinear system; Self-synchronization; Computer simulation; DC motors; Electric excitation; Electric power supplies to apparatus; Kinematics; Mathematical models; Numerical analysis; Synchronization; Torque; Vibrations (mechanical); Duffing system; Non-ideal systems; Nonlinear systems